2020
DOI: 10.3390/app10062110
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Roughness Measurement of Railhead Surface Using an Optimal Sensor Batch Algorithm

Abstract: Contact and friction between wheel and rail during train operation is the main cause of the rolling noise for which railways are known. Therefore, it is necessary to accurately measure the surface roughness of wheels and rails to monitor railway noise and predict noise around tracks. Conventional systems developed to measure surface roughness have large deviations in measured values or low repeatability. The recently developed automatic mobile measurement platform known as Auto Rail Checker (ARCer) uses three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The treated blade has an RMS roughness of ∼850 nm (measured with an optical profilometer), close to the railhead’s typical roughness of 1 μm. 19
Figure 1.Schematic of the laboratory apparatus. The wheel represents the train wheel, and the blade represents the rail.
…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…The treated blade has an RMS roughness of ∼850 nm (measured with an optical profilometer), close to the railhead’s typical roughness of 1 μm. 19
Figure 1.Schematic of the laboratory apparatus. The wheel represents the train wheel, and the blade represents the rail.
…”
Section: Methodsmentioning
confidence: 94%
“…The treated blade has an RMS roughness of ∼850 nm (measured with an optical profilometer), close to the railhead's typical roughness of 1 μm. 19 The wheel design was based on the work conducted by Naeimi et al, 20 where they showed that a 1/5-scale train wheel under scaled loading could produce a contact pressure comparable to that at the wheel-rail interface. The wheel diameter is 0.2 m (roughly 1/5 of the actual wheel diameter).…”
Section: Lab Experimentsmentioning
confidence: 99%
“…Kampczyk [ 11 ] presents the analysis and evaluation of the turnout geometry conditions, also describing the causes of turnout deformations. Researchers such as Wootae Jeong and Dahae Jeong [ 12 ] present a method for accurately measuring the roughness of wheels and rails, considered the main cause of producing the noise during trains operation. They propose enhancing the chord offset synchronization algorithm applied to the existing ARCer for high measurement precision with only two displacement sensors.…”
Section: Related Workmentioning
confidence: 99%
“…Experiments were performed to find the influence of temperature on modal properties used for damage diagnosis. Jeong and Jeong [12] proposed an optimization method for sensor batch design to measure roughness on railhead surfaces. This information allowed the estimation of corrugations and contact between wheel and rail during train operation to analyze rolling noise.…”
Section: Sensors Parameter Identification and Signal Processingmentioning
confidence: 99%